1988
DOI: 10.1128/mcb.8.4.1525-1533.1988
|View full text |Cite
|
Sign up to set email alerts
|

Double Minute Chromosomes Can Be Produced from Precursors Derived from a Chromosomal Deletion

Abstract: Recent experiments have shown that gene amplification can be mediated by submicroscopic, autonomously replicating, circular extrachromosomal molecules. We refer to those molecules as episomes (S. Carroll, P. Gaudray, M. L. DeRose, J. F. Emery, J. L. Meinkoth, E. Nakkim, M. Subler, D. D. Von Hoff, and G. M. Wahl, Mol. Cell. Biol. 7:1740-1750, 1987). The experiments reported in this paper explore the way episomes are formed and their fate in the cell over time. The data reveal that in our system the episomes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Episomes were isolated by denaturation and renaturation of DNA and visualized by gel electrophoresis. This work led to the development of an episome model in cancer genetics that states that episomes are formed by excision of linear DNA from chromosomes followed by circularization and amplification [4,[32][33][34]. ecDNA Next-generation sequencing (NGS)-based studies have in recent years allowed scientists to study the sequences of circular DNA from tumors in-depth.…”
Section: Episomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Episomes were isolated by denaturation and renaturation of DNA and visualized by gel electrophoresis. This work led to the development of an episome model in cancer genetics that states that episomes are formed by excision of linear DNA from chromosomes followed by circularization and amplification [4,[32][33][34]. ecDNA Next-generation sequencing (NGS)-based studies have in recent years allowed scientists to study the sequences of circular DNA from tumors in-depth.…”
Section: Episomesmentioning
confidence: 99%
“…Circularization could be mediated by the DNA repair pathways also involved in forming small eccDNA, as described previously. In some cases, ecDNA is suggested to arise by multistep processes, potentially from smaller precursors [32,40]. In others, large-scale DNA damage events have been proposed as the sources of ecDNA in cancer.…”
Section: Trends In Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the events result in DNA sequence amplification at the telomeres that eventually loops out to form eccDNAs [59]. The fourth model is the episome model, which explains that excision of small circular DNA results in episome formation, which eventually results in recombination or over-replication, resulting in eccDNA formation [34,60]. It is well known that eccDNAs can lead to mutations, amplifications, translocations, deletions, etc.…”
Section: Recent Advances In Eccdnamentioning
confidence: 99%
“…It can be derived from everywhere in a genome with sizes ranging from hundreds of base pairs (bp) to several mega bases (Mb). According to the size and origin, eccDNAs can be categorized into mitochondria DNAs (mtDNAs), episomes, double minutes (DMs) (100kb∼3 Mb), telomeric circle (t-circles), small polydispersed circular DNA (spcDNA) (100bp∼10 kb), and microDNA (100–400 bp) ( Wang M et al, 2021 ).Some studies revealed that episomes can be polymerized into DMs in cancer cells suggesting the possibility that one type of eccDNA can be transformed to others by polymerization or fragmentation with subsequent recircularization ( Wahl et al, 1984 ; Carroll et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%